PENGARUH REKRUTMEN DAN SELEKSI TERHADAP KINERJA KARYAWAN PADA PT. NUSANTARA INDAH MAZDA DI SAMARINDA - Luqman Al'quran (OBOR: Oikonomia Borneo, 2019)
This study aims to determine the system of recruitment and selection and to determine the process of recruitment and selection of the work performance of employees at PT. Nusantara Indah Mazda in Samarinda. In this study using a simple regression analysis tool in the calculations assisted by the SPSS (Statistical Product and Service Solutions) program. With the equation (Y=a+bX), where Y is the dependent variable, namely employee performance, X is the independent variable, namely the recruitment and selection process, a is a constant which is the average value of Y when the values ​​of X1 and X1 are equal to zero and b as a partial regression coefficient, measuring the average value of Y for each change in X1 by assuming that X1 is constant. From the results of the analysis, it is known that recruitment and selection have no significant effect on employee performance at PT. Nusantara Indah Mazda Samarinda where recruitment is the process of obtaining a number of qualified human resources (employees) to occupy a position or job in a company and selection is the process of obtaining and using information about job applicants to determine who should be accepted for short-term positions and long-term. Through the results of the partial test that has been carried out, it turns out that there is no significant effect between recruitment and selection on employee performance with a level of significance. (X)t < t , that is -0.636 < 1.693 so that it can be seen that recruitment and selection variables have a negative effect and the hypothesis expressed by the author is accepted that there is an influence of recruitment and selection on employee performance at PT. The beautiful archipelago of Mazda samarinda.